Effects of Thidiazuron and Pollinator visits on Fruit Set and Quality of 'Maxigala' Apple Trees - Bizotto, Lucas de Almeida; Santos, Régis Sivori Silva dos; Boff, Mari Ines Carissimi (Comunicata Scientiae, 2024)
The objective of this study was to assess the effects of thidiazuron (TDZ) application and pollinator visits on fruit set and quality in apple trees of the cultivar Maxigala. The experiment was conducted at the Temperate Fruit Farming Experimental Station of the Brazilian Agricultural Research Corporation (EMBRAPA Grape and Wine), in Vacaria, RS, Brazil. The evaluated treatments were: TDZ application; floral visitors combined with TDZ application; floral visitors; and control (no floral visitors with no TDZ application). The highest mean final fruit set was found for the treatment with only TDZ application, followed by that with floral visitors and TDZ application.